Experience, decision‐making and information needs around parenteral nutrition among people with advanced cancer, and their carers: A scoping review. Issue 2 (3rd November 2022) - McCracken, Jennifer; Wheelwright, Sally; Hon, YiWen; Shaw, Clare
Abstract: Background: The present study aims to summarise current knowledge and identify gaps in knowledge and research regarding experience, decision‐making and information needs around parenteral nutrition, among people with advanced cancer, and their carers. Methods: This review was informed by previous methods and guidance on conducting and reporting scoping reviews. A literature search was conducted in March 2021 using Embase, Medline, CINAHL, Google and Web of Science to identify studies that examined the experience, decision‐making process and information needs of adults with advanced cancer, and their carers, who were making decisions around commencing and discontinuing parenteral nutrition. There were no date limitations, although only papers published in English were included. Results: Of the 588 papers identified, 12 papers, all qualitative, met the eligibility criteria. Despite the reported negative aspects of home parenteral nutrition, patients and carers felt the benefits outweighed these. There was variability in whether patients and carers felt involved in decisions around commencing parenteral nutrition. No studies specifically addressed information needs. Conclusions: Research is required to explore the information that patients with advanced cancer, and their carers, need to facilitate their decision‐making around commencing and discontinuing parenteral nutrition. We recommend the development of processes for obtaining written informed consent from patients commencing parenteral nutrition to ensure that core topics are discussed on initiation, enabling patients and carers to make informed decisions. Additionally, we recommend development of a national framework to inform patients and carers of the whole discharge process on PN from decision‐making to discontinuing PN. Abstract : Experience, decision‐making and information needs around parenteral nutrition among people with advanced cancer, and their carers Key points: Carers would like to receive more information around home parenteral nutrition. No studies have specifically explored the information needs of patients with advanced cancer and their carers making decisions around parenteral nutrition. The best ways to communicate information around parenteral nutrition to patients and carers are unknown. Patients should be asked if they wish to involve a carer in decision‐making. Reasons for stopping parenteral nutrition are not routinely discussed with patients. The rationale for stopping parenteral nutrition should be discussed at its initiation. We recommend the development of procedures for obtaining written informed consent from patients commencing parenteral nutrition. We recommend the development of a national, standardised framework outlining the discharge process for patients with advanced cancer on home parenteral nutrition. Research is required to explore the information that patients with advanced cancer, and their carers, need to facilitate their decision‐making around commencing and discontinuing parenteral nutrition.